Ano5 deficiency inhibits osteoclastogenesis and reduces ovariectomy-induced bone loss by regulating the ACSL4-dependent ferroptosis pathway - Mingyue Zhang; Huichong Xu; Kaiwen Sun; Shuai Zhang; Shengnan Wang; Liqi Lin; Hongyu Li; Ying Hu (Tissue and Cell, 2026)

A pomegranate-inspired B@(NH4)2SiF6@LiClO4 architecture for spatiotemporally coordinated boron combustion - Jiayan Liang; Hongyu Zhang; Jian Zhang; Xuwen Wang; Yangming Wang; Hao Bai; Yi Rong; Kaifeng Lin; Debin Xia; Yulin Yang (Chemical Engineering Journal, 2026)

Effects of different urea-based fertilizers on gaseous and hydrological nitrogen losses from subtropical citrus orchards - Jing Zheng; Hongyu Lin; Xingling Wang; Hongyang Dong; Bowen Zhang; Hui Cheng; Shouzheng Jiang; Ralf Kiese; Klaus Butterbach-Bahl; Minghua Zhou (Agriculture, Ecosystems & Environment, 2026)

Deep eutectic solvent plasticization of chitosan/distiller's grains prolamin films: Hydrogen bond-driven structural regulation and enhanced food preservation performance - Lin Deng; Haoyang Sun; Xiaomeng Li; Yi Sun; Yarong Wang; Hongyu Yang; Jian Su; Long Sheng; Jia Zheng; Zhaoxia Cai (Food Research International, 2026)

A systemic nanozyme therapeutic disrupts the ROS-inflammation circuit to prevent multi-organ injury - Yan Huang; Yixiao Liu; Rongrong Wu; Hongyu Yan; Zixuan Li; Yuanyi Zheng; Xiaojun Cai; Lin Chen (Chemical Engineering Journal, 2026)

Voltage-gradient-driven microbial selection and functional gene abundance elucidate aniline and nitrogen degradation in algal-bacterial symbiotic systems - Bing Lin; Qian Zhang; Xiangyu Liu; Hongyu Wang; Bin Ji (Algal Research, 2026)

Soybean drought recognition method based on multi-view 3D image Fourier transform - Yingying Cheng; Haiou Guan; Xiaodan Ma; Hongyu Lin (Computers and Electronics in Agriculture, 2026)

C-type lectins in arthropods: Evolutionary diversification and prospects for pathogen defense - Hongyu Li; Jialu Xu; Hairun Li; Jiyuan Wang; Xintong Chen; Yijie Zhang; Mingcheng Liu; Xiaofen Zhang; Yuqing Wang; Yunhuan Zhu; Yuncheng Qian; Yajie Lin; et al. (Journal of Invertebrate Pathology, 2026)

Fluorene-containing poly(aryl ketone) membranes with high-density sulfonation and improved stability for proton exchange membrane fuel cells - Qiang Ren; Wenying Li; Liyuan Chen; Ziyu Lin; Hongyu Pan; Zhiwei Zhao; Guannan Chen; Jinhui Pang; Zhewen Liu; Zhenhua Jiang (Chemical Engineering Journal, 2026)

Molecular Insights into Phenolic Polymerization during the Transition from High-Valent Iron Oxidation to Electron Transfer - Hai Kuang; Ruike Men; Jianying Wu; Lin Li; Yinhao Dai; Peiren Ding; Lushi Lian; Hongyu Dong; Xiaohong Guan (Water Research, 2026)

A multi-stage event-preserving denoising approach for microseismic signals via fusion of WOA–VMD, PSR, and AWMF - Hongyu Xu; Feng Dai; Yi Liu; Lin Liang; Dingran Song; Mingdong Wei (Tunnelling and Underground Space Technology, 2026)

Early-Life Stages Amplify the Ecotoxicological Vulnerability of Freshwater Gastropods to the Agricultural Fungicide Prochloraz - Jiyuan Wang; Hairun Li; Jialu Xu; Yanlai Yao; Linwei Chen; Ruke Wang; Yuqing Shao; Lu Yang; Xiaofen Zhang; Xiaodong Yao; Lijun Lin; Hongyu Li (Journal of Hazardous Materials, 2026)

Osteoprotective effect of Perinereis aibuhitensis ultrasound-assisted aqueous extract against retinoic acid-induced osteoporosis in mice - Biliang Mo; Xinxia Song; Jianmeng Liao; Xiaoyu Xia; Hongyu Lu; Wenhong Cao; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Zhihong Zheng; et al. (Food Bioscience, 2026)

Microbial carbon use efficiency is crucial to support higher SOC content in old-growth forests: evidence from subalpine coniferous forests on the eastern edge of the Qinghai-Tibet plateau assessed by three approaches - Shenglan Ma; Wanze Zhu; Hongyu Lin; Wenwu Wang; Xia Li; Wolfgang Wanek (Plant and Soil, 2026)

Microbial carbon use efficiency, not extracellular enzyme stoichiometry, shows negligible response to alpine tunnel construction - Jiarui Tian; Yan Yue; Hongyu Lin; Yixuan Cheng; Yuzhuo Chen; Jincheng Xiang; Benjamin Laffitte; Xiangjun Pei; Xiaolu Tang (Journal of Environmental Management, 2026)

A recognition method of soybean varieties based on near-infrared spectroscopy and improved deep learning model - Haiou Guan; Hongyu Lin; Xiaodan Ma; Jiao Yang; Yiwen Zhao; Yingying Cheng (Food Chemistry, 2026)

Hybrid NiFe-LDH/SnO2 modified ceramic membrane with dual-functional enhancement in catalytic ozonation and synergistic anti-fouling for efficient wastewater decontamination - Jyunhong Shen; Antong Shi; Weijian Nian; Zhihao Lin; Rongjie Wu; Hao Shen; Zhang Yan; Hongyu Zhang; Zhi Zhang; Gongduan Fan; Zhuwu Jiang (Desalination, 2026)

Dynamics of kinetic energy in rill headcut erosion and sediment yield characteristics within granitic red soil regions - Shuyu Luo; Jianyu Wang; Zhe Lin; Jiangxing Wei; Wencong Liang; Hongyu Liu; Fang Wang; Guiwan Yan; Shuting Liu; Xiaoqian Duan; Yusong Deng (CATENA, 2026)

Divergent temporal evolution of potentially toxic elements contamination and health risks in agricultural soils around active and decommissioned uranium mines - Kunjie Chen; Hongyu Wen; Binghao Huang; Wufeng Zheng; Yujia Lin; Zeyue Huang; Jingye She; Mingliang Kang; Guiyuan Liang; Wentao Chen; Hanyu Wu (Environmental Geochemistry and Health, 2026)

Experimental investigation of nonlinear hydrodynamic properties of the T-foil on a high-speed trimaran - Shijie Liu; Lincen Han; Hongyu Lin; Shaoqing Liu; Xi Chen; Yichen Jiang (Ocean Engineering, 2026)

Degradation performance and mechanism of pyridine and 2-diethylamino-4‑hydroxy-6-methylpyrimidine by Pandoraea captiosa HR2 in individual or simultaneous systems - Hongyu Niu; Wencong Lin; Songyan Zhu; Weitao Liu; Shiqiang Tian; Haijun Yang; Rilong Zhu (Journal of Environmental Sciences, 2026)

Analysis of nitrogen distribution in chemical looping gasification of kitchen waste and soy protein as a model compound with CuFe2O4 and NiFe2O4 oxygen carriers - Shiwen Fang; Luzhou Ding; Yan Lin; Shuchang Yan; Xiongwei Zheng; Zhen Huang; Hongyu Huang (Fuel, 2026)

Electric field drives assimilation enhancement and deterministic assembly in algae-bacteria symbiosis for enhanced aniline biodegradation - Bing Lin; Qian Zhang; Xiangyu Liu; Nanping Wu; Hongyu Wang; Bin Ji (Bioresource Technology, 2026)

Dolomite in conjunction with straw application increased straw-derived CO2 emission while depressed soil organic carbon mineralization in two acidic paddy soils - Peng Xu; Hongtao Wu; Mengdie Jiang; Tao Jin; Bo Zhu; Zhangyong Liu; Hongyu Lin; Ronggui Hu (Biology and Fertility of Soils, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

Genetic diversity analysis of three geographical populations of Triplophysa yarkandensis macroptera in arid northwestern China - Ya Liu; Hangyu Lin; Hongyu Ke; Han Zhao; Zhongmeng Zhao; Shengqi Su; Qiang Li (Journal of Arid Environments, 2026)

Selective degradation of tetracyclines in the Mn(II)/H2O2/HCO3 process with low peroxide dosage: The neglected role of complexation-mediated electron transfer - Yimin Lin; Ruike Men; Yinhao Dai; Ivan P. Pozdnyakov; Hongyu Dong; Xiaohong Guan (Journal of Hazardous Materials, 2026)

Performance prediction of electrochemical degradation of monochloroacetamide (MCAcAm) using machine learning models - Mengyu Liu; Li Lin; Caihong Yu; Wenbin Zheng; Hongyu Zhang; Zhuwu Jiang; Huabin Liu (Journal of Environmental Chemical Engineering, 2026)

Dynamic changes in volatile organic compounds and microbial community of snakehead segments coated with a gallic acid–embedded edible film - Hongyu Jiang; Wang Li; Haonan Gong; Enhao Yao; Chaofan Ji; Xinping Lin; Beiwei Zhu; Sufang Zhang (Food Research International, 2026)

Challenges and solutions in seismic geomorphology of ultra-deep carbonates: insights from the Cambrian Longwangmiao formation, central Sichuan Basin, China - Lei Tan; Xiao Feng; Gang Zhou; Lin Qiao; Ya Zhang; Hongyu Long; Hong Liu; Minxing Li; Jianbo Huang (International Journal of Earth Sciences, 2026)

Biofloc Technology Improves Harmful Nitrogen and Pathogens Control and Enhances Production Performance in Intensive Penaeus vannamei Culture Ponds with Reduced Water Exchange - Shuangyin Li; Hongyu Liu; Yiji Lin; Yucheng Cao; Guoliang Wen; Haochang Su; Xiaojuan Hu; Yu Xu; Keng Yang; Wujie Xu (Fishes, 2026)
This 90-day trial evaluated the integrated benefits of biofloc technology (BFT) in lined ponds for intensive Penaeus vannamei culture, comparing it with a conventional water-exchange (WE) system. The BFT system maintained favorable water quality with a 68.4% reduction in cumulative water exchange. Concentrations of toxic total ammonia–nitrogen (TAN) and nitrite–nitrogen (NO2−-N) were better controlled, and total suspended solids (TSS) stabilized within a beneficial range (150–200 mg L−1). Microbial analysis indicated that BFT significantly increased total bacterial abundance in both culture water and shrimp hepatopancreas while reducing the total Vibrio-to-bacteria ratio in culture water to below 6%, significantly lower than in the WE system (>18%). Moreover, BFT significantly lowered the loads of specific pathogens, acute hepatopancreatic necrosis disease (AHPND)-causing Vibrio parahaemolyticus, and Enterocytozoon hepatopenaei (EHP) in both culture water and shrimp hepatopancreas. Regarding production performance, BFT significantly enhanced shrimp survival rate (82.4% vs. 71.5%), yield (3460 vs. 2948 kg pond−1), and water productivity (0.85 vs. 0.28 kg m−3), while lowering the feed conversion ratio (1.16 vs. 1.33). In conclusion, BFT achieves stable water quality, effective pathogen suppression, and enhanced production efficiency through microbial regulation, offering a viable water-saving, environmentally sound, and disease-resilient strategy for intensive P. vannamei culture.

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

From fat to fate: how aging adipose tissue drives systemic metabolic aging - Haiyan Lin; Hongyu Li; Qiang Tang (Biogerontology, 2026)

A comparative analysis of immune memory in bivalve and gastropod Mollusks: From mechanistic insights to practical applications - Hongyu Li; Hairun Li; Ling Zhao; Jialu Xu; Xianwei Li; Qingzhi Zhao; Yijie Zhang; Yuqing Shao; Ruke Wang; Jiyuan Wang; Lijun Lin; Xiaodong Yao; et al. (Aquaculture, 2026)

Stage-specific neurotoxicity of lead in zebrafish: Metabolic disruption in embryos and ferroptosis in larvae - Jian Liu; Guizhen Yan; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

Soil aggregates, carbon and nitrogen content, and water retention across land uses in the Reshui River Catchment - Jing Zheng; Jianxiong Zhang; Bing Ren; Hongyu Lin; Ziyang Li; Feng Gu; Bo Zhu; Barthelemy Harerimana; Minghua Zhou (Ecological Engineering, 2026)

Balancing traffic efficiency and ecosystem services in road network planning: A spatial multi-objective optimization approach - Yuxiang Dong; Yuxin Ding; Hongyu Chen; Chensong Lin; Longfeng Wu (Journal of Environmental Management, 2025)

Biomineralization-driven simultaneous carbon/phosphorus recovery and membrane fouling control in anaerobic membrane bioreactor for swine wastewater treatment - Qianyi Liu; Hongyu Xie; Yin Xu; Ziang Zhou; Yuqi Chen; Lan Lin; Rasheed Adeleke; Heng Li; Yuanpeng Wang; Shaohua Chen; Yanlong Zhang (Water Research, 2025)

Competitive blockade of NKCC1 by potassium suppresses thallium bioaccumulation and neurotoxicity in zebrafish: Implications for aquatic toxicity - Jian Liu; Xin Li; Yiwen Zhu; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Science of The Total Environment, 2025)

Influence of initial headcut height on rill headcut erosion mechanisms via runoff hydrodynamics modulation in granite residual soil - Jianyu Wang; Zhe Lin; Jiangxing Wei; Wencong Liang; Hongyu Liu; Fang Wang; Guiwan Yan; Shuting Liu; Xiaoqian Duan; Yusong Deng (Journal of Hydrology, 2025)

Gradual succession of dominant pathway from autotrophic to heterotrophic metabolism with the increment of C/N in pyrite-based biofilm-electrode reactor (PBER) - Lin Tan; Zhiyuan Wang; Hongyu Wang; Shiyang Zhang; Wenjiao Sang; Qian Zhang; Xinhua Tang; Qianjin Dong (Environmental Research, 2025)

Spatial patterns of soil carbon and nutrient distribution during vegetation restoration in red soil regions - Hongyu Liu; Zhe Lin; Wanxia Huang; Dalan Liao; Xiaoqian Duan; Yusong Deng (Plant and Soil, 2025)

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

Construction of island ecological security pattern under multi-circle development pattern: Evidence from Hainan Island - Sizheng Li; Feng Gui; Hongyu Li; Yanwei Song; Linhao Peng; Lin Zhou; Yang Wang (Ocean & Coastal Management, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Exploring efficient chlorine evolution reaction with Ru-RuO2/C@TiC electrodes in antibiotic degradation under saline conditions - Zhehan Tu; Zhuwu Jiang; Weixin Lin; Jiahan Yang; Fengying Zhang; Xue Bai; Jyunhong Shen; Hongyu Zhang; Huabin Liu (Process Safety and Environmental Protection, 2025)

Hydrogel-engineered platforms for efficient solar interfacial evaporation: Current status and future directions - Junnan Jiang; Heyu Jin; Yao Lu; Xiaohua Liu; Hongyu Ge; Lin Mu (Journal of Water Process Engineering, 2025)

Airborne human-associated ARGs in municipal wastewater treatment plants - Ying Wang; Yunping Han; Lin Li; Jianwei Liu; Hongyu Tian (Journal of Hazardous Materials, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

The role of light intensity in an electrically enhanced algal activated sludge (E-AAS) system for the treatment of aniline wastewater: Effects on bacterial-algal synergies and electron transport - Xunhao Liu; Qian Zhang; Meng Li; Bing Lin; Qi He; Nanping Wu; Jiajing Chen; Xiaoqian Dong; Hongyu Wang (Journal of Water Process Engineering, 2025)

Unexpected tetracycline antibiotics degradation in the Fenton process under near-neutral pH conditions: Performance and mechanism - Hongyu Dong; Yimin Lin; Mingyang Feng; Yinhao Dai; Zhenhua Dai; Xiaoguang Duan; Raf Dewil; Xiaohong Guan (Journal of Hazardous Materials, 2025)

A novel synthetic 3,4,5-tri-feruloylquinic acid enhances learning and memory via neurotrophin signaling in an aging model senescence-accelerated prone 8 mice - Hongyu Lin; Kazunori Sasaki; Farhana Ferdousi; Shinji Kondo; Hiroko Isoda (GeroScience, 2025)
This study is the first to investigate the anti-aging effects of the newly synthesized compound, 3,4,5-tri-feruloylquinic acid (TFQA), in vivo using the senescence-accelerated mouse prone 8 (SAMP8) model, through integrated whole-transcriptomic and biochemical analyses. Oral administration of TFQA (1 mg/kg body weight) for 37 days led to significant cognitive improvements, as demonstrated by enhanced performance in the Morris water maze (MWM) test, including reduced escape latency and increased time spent in the target zone, target crossings, distance traveled, and swimming speed. Gene Ontology (GO) analysis of hippocampal microarray data revealed that TFQA upregulated genes associated with neurotransmitter and synaptic functions, while downregulating inflammatory pathways. Protein–protein interaction (PPI) analysis indicated that neurotrophin signaling was a critical upstream regulator in TFQA-treated mice. Further biochemical validation showed elevated levels of neurotransmitters (serotonin, noradrenaline, and dopamine) in the brain. Additionally, mRNA expression of tumor necrosis factor ( Tnf ), an inflammatory cytokine, was significantly reduced in the brain. Examination of the neurotrophins involved in neurotrophin signaling revealed that TFQA most prominently regulated brain-derived neurotrophic factor ( Bdnf ) co-expressed genes, which was validated by increased B dnf expression in both the brain and serum of SAMP8 mice. Bioluminescence imaging demonstrated that a single oral dose of TFQA significantly increased BDNF expression in the brains of BDNF-IRES-AkaLuc mice. Binding studies showed that TFQA has a strong affinity for the tyrosine receptor kinase B (TrkB) receptor. In summary, TFQA holds potential as a neuroprotective agent, mitigating learning and memory deficits in aging mice via neurotrophin signaling, particularly through BDNF upregulation. Graphical Abstract

Distinct neurotoxic mechanisms of thallium and lead: Calcium-mediated apoptosis and iron-induced ferroptosis in zebrafish at environmental concentrations - Jian Liu; Ai Guan; Zihui Huo; Xin Li; Yiwen Zhu; Hongwei Liang; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2025)

Developmental toxicity and environmental risk assessment of chlorothalonil: A comprehensive study using biomphalaria as a model gastropod - Hongyu Li; Ruiqi Weng; Hao Wu; Xianwei Li; Jiyuan Wang; Jialu Xu; Qingzhi Zhao; Yunhuan Zhu; Yuncheng Qian; Yijie Zhang; Xiaofen Zhang; Lijun Lin; et al. (Journal of Hazardous Materials, 2025)

Novel ductile and durable engineered cementitious composite columns reinforced with steel-FRP composite bars: Axial compression behavior and design - Yulei Bai; Qipeng Ma; Shiwen Han; Lin Yang; Yufeng Zhang; Hongyu Zhang (Engineering Structures, 2025)

Proteoglycans and glycosaminoglycans: critical regulators in angiogenesis, vasculogenesis, and vascularized tissue engineering - Binbin Lin; Tianyu Sun; Yiqi Feng; Hongyu Liu; Lingling Zhang; Buling Wu; Jingyi Wu (Angiogenesis, 2025)

A single-objective Sequential Search Assistance-based Multi-Objective Algorithm Framework - Peng Chen; Jing Liang; Kangjia Qiao; Xuanxuan Ban; P.N. Suganthan; Hongyu Lin; Jilong Zhang (Swarm and Evolutionary Computation, 2025)

A method for evaluating the failure state of geomaterials in DEM by introducing equivalent Cauchy stress and macro strength criterion - Hongyu Dong; Qingtao Lin; Dechun Lu; Fujun Zhang; Xiuli Du (Computers and Geotechnics, 2025)

eDNA Metabarcoding Reveals the Depth-Structured Variation of Coral Reef Fish - Jinfa Zhao; Lin Lin; Yong Liu; Teng Wang; Yu Liu; Yayuan Xiao; Jianzhong Shen; Hongyu Xie; Hai Huang; Qiuying Han (Fishes, 2025)
Global coral reef ecosystems face various levels of disturbance pressure. Understanding the depth-structured variation in coral reef fish communities can help us to better grasp and predict the adaptive changes of the ecosystem under different stressors. This study applied eDNA metabarcoding technology to analyze the spatial distribution of the coral reef fish at various depths (0 m, 5 m, 10 m, 15 m, 20 m, 30 m, 40 m, 50 m, and 60 m) within the Xisha Islands of China. The results indicated that the eDNA technology detected a total of 213 amplicon sequence variants (ASVs), including 33 species that were not identified using traditional methods. Herbivorous fish generally dominated in relative abundance across different depths. Moreover, the similarity among depth groups was largely absent, and significant differences existed in fish assemblages across depth gradients, consistent with the unique depth preferences of fish microhabitats. Importantly, our findings revealed distinct depth-structured variation among different functional groups of coral reef fish. Large carnivorous fish initially increased and then decreased along the depth gradient from 0 to 60 m, with a turning point around 20 m, while large herbivorous fish displayed the opposite trend. Small carnivorous and small herbivorous fish consistently declined along the same depth gradient. Additionally, the Margalef index (D) and Function richness (FRic) both displayed a consistent downward trend with increasing depth, while the Shannon–Wiener index (H′), Pielou index (J′), Quadratic entropy (RaoQ), Functional dispersion (FDis), and Functional evenness (FEve) initially increased and then decreased, peaking around 20 m. This study revealed that eDNA metabarcoding is an effective tool for evaluating coral reef fish biodiversity, community composition, and spatial distribution. It enhances our understanding of distribution dynamics and offers valuable insights for coral reef conservation and restoration efforts.

Quality assessment and microbial community succession of finely chopped common carp (Cyprinus carpio) under low-temperature storage: Implications for nutritional composition and spoilage indicators - Haonan Gong; Binchen Wang; Hongyu Jiang; Wang Li; Yujiao Zhang; Chaofan Ji; Xinping Lin; Sufang Zhang (Food Control, 2025)

Integration of microbiomics and metabolomics reveals energy metabolism imbalance in crucian carp (Carassius auratus) under saline-alkaline exposure - Lin Han; Wenzhi Liu; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Mechanism of blocking the glutamate pathway to exacerbate oxidative stress, ammonia toxicity and metabolic disorders in crucian carp (Carassius auratus) under saline-alkaline exposure - Wenzhi Liu; Lin Han; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Operant social seeking to a novel peer after social isolation is associated with activation of nucleus accumbens shell in rats - Adedayo Olaniran; Kristine T. Garcia; Megan A. M. Burke; Hongyu Lin; Marco Venniro; Xuan Li (Psychopharmacology, 2025)

Study on the moisture adsorption characteristics of AlPO4-LTA and its dehumidification performance in desiccant coated dehumidifier - Yaofeng Zhang; Lin Liu; Peng Liu; Lisheng Deng; Jun Li; Xiaofeng Guo; Yugo Osaka; Hongyu Huang (International Journal of Refrigeration, 2025)

Hierarchical model with integrated probabilistic strategy for classifying pig behaviors using active electronic ear tags - Junyong Lin; Runkang Wu; Ling Yin; Xueyin Wang; Hongyu Chen; Gengyuan Cai; Zhenfang Wu; Ming Yang; Jie Yang; Sumin Zhang (Computers and Electronics in Agriculture, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Effect of oxidation on finely segmented products of snakehead: Digestibility and microstructure - Hongyu Jiang; Wang Li; Haonan Gong; Chaofan Ji; Xinping Lin; Beiwei Zhu; Sufang Zhang (Food Chemistry, 2025)

Subnanometer ultra-thin magnetic nanosheets for highly sensitive magnetic resonance angiography - Kun Liu; Na Yang; Chunmin Bo; Xianglong Zhu; YiFan Fan; Hong Hao; Zhen Jin; Jinhao Gao; Hongyu Lin; Chunli Wang (Chemical Engineering Journal, 2025)

Comparative analysis of embryonic development and growth performance among two mud crab species and their hybrids - Yang Zhao; Waqas Waqas; Wenxiao Cui; Shaopan Ye; Weifeng Gao; Qingyu Zhang; Zhen Lin; Di Zhu; Feng Lin; Mhd Ikhwanuddin; Hongyu Ma (Aquaculture, 2025)

Enhanced priming effect in agricultural soils driven by high-quality exogenous organic carbon additions: A meta-analysis - Yuyao Zhang; Hongyu Hu; Yiguo Ran; Ping Huang; Yunlong Cai; Lin Chen; Congzhi Zhang; Xin Gao; Donghao Ma; Jiabao Zhang (Science of The Total Environment, 2025)

The profound review of Fenton process: What's the next step? - Yimin Lin; Junlian Qiao; Yuankui Sun; Hongyu Dong (Journal of Environmental Sciences, 2025)

Preparation of a novel organic-inorganic composite sludge bioflocculant (SBF) from dewatered sludge as raw material: Characteristics, flocculation mechanism and application for domestic sewage - Jingyun Ge; Hongyu Tian; Lin Li; Yunping Han; Jianwei Liu (Bioresource Technology, 2025)

Optimized green infrastructure planning at the city scale based on an interpretable machine learning model and multi-objective optimization algorithm: A case study of central Beijing, China - Hongyu Chen; Yuxiang Dong; Hao Li; Shuangzhi Tian; Longfeng Wu; Jinlong Li; Chensong Lin (Landscape and Urban Planning, 2024)

Exploring the impact of visible light intensity on algae-bacterial symbiotic system treating aniline wastewater: Performance, microbial community and metabolic pathways - Jiajing Chen; Qian Zhang; Meng Li; Jing He; Bing Lin; Nanping Wu; Xunhao Liu; Siwei Li; Jialong Huang; Xiaoqian Dong; Hongyu Wang (Journal of Water Process Engineering, 2024)

Deep dehumidification characteristics of a silica gel coated cross-flow heat exchanger with a circulating blowing loop - Lin Liu; Hongyu Huang; Jun Li; Yu Bai; Zhaohong He; Lisheng Deng; Tieyu Gao; Mitsuhiro Kubota; Noriyuki Kobayashi (Energy and Buildings, 2024)

Loss prediction of carbon stocks caused by Spartina alterniflora clearing in coastal wetlands of Yancheng, China - Mengyuan Su; Yufeng Li; Chunqi Qiu; Yong Zhou; Lin Li; Yue Jia; Jingjing Ding; Zhaoyuan Yu; Alan Wright; Hongyu Liu (Geo-Marine Letters, 2024)

TROPOMI unravels transboundary transport pathways of atmospheric carbon monoxide in Tibetan Plateau - Peize Lin; Yuan Tian; Tobias Borsdorff; Zhiwei Li; Jochen Landgraf; Hongyu Wu; Jingkai Xue; Dake Ding; Hang Ye; Yizhi Zhu; Cheng Liu (Science of The Total Environment, 2024)

Activation of peroxymonosulfate by novel magnetically recyclable CoFe2O4/MXene quantum dots composites for rapid degradation of tetracycline: Synergistic performance and mechanisms - Zhenyu Guo; Haiyi Jin; Hongyu Sun; Bisheng Li; Huadong Yu; Die Ling Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

Rapid and simultaneous detection of cadmium and mercury in foods based on solid sampling integrated electrothermal vaporization technique - Hongyu Jia; Guanyu Lan; Xue Li; Lin Chen; Li Feng; Xuefei Mao (Food Chemistry, 2024)

Improved activity and significant O2 resistance of Cs doped Co3O4 catalyst for N2O decomposition - Hongyu Zhao; Pan Wang; Zonglin Li; Chengcheng Ao; Xuteng Zhao; He Lin (Journal of Environmental Chemical Engineering, 2024)

Removal performance of Nitrogen, sulfur and chlorine pollutants during chemical looping combustion of textile dyeing sludge using red mud as an oxygen carrier - Hongming Jiang; Yan Lin; Na Gao; Shiwen Fang; Duo Li; Zhen Huang; Hongyu Huang (Chemical Engineering Journal, 2024)

Synergistic interaction of vortex capture and fluid shear in Ni-rich cathode precursor growth process - Yuting Deng; Yi Wang; Lang Qiu; Hongyu Lin; Mengke Zhang; Junbo Zhou; Fuqiren Guo; Benhe Zhong; Yang Song; Xiaodong Guo (Chemical Engineering Journal, 2024)

Long non-coding RNA MAGEA4-AS1 binding to p53 enhances MK2 signaling pathway and promotes the proliferation and metastasis of oral squamous cell carcinoma - Xiaoxiao Wei; Zhangfu Li; Heng Zheng; Xiaolian Li; Yuntao Lin; Hongyu Yang; Yuehong Shen (Functional & Integrative Genomics, 2024)

Divergent rainfall infiltration patterns on the Chinese Loess Plateau between growing and non-growing seasons after long-term revegetation - Ruoxuan Li; Bihang Fan; Zhao Jin; Mingkui Hao; Hu Liu; Yaling Zhang; Yanjia Jiang; Hongyu Yao; Ke Lin; Li Guo (Journal of Hydrology, 2024)

Metformin improves insulin resistance, liver healthy and abnormal hepatic glucolipid metabolism via IR/PI3K/AKT pathway in Ctenopharyngodon idella fed a high-carbohydrate diet - Lixian Li; Ling Pan; Zhixuan Lin; Jiasheng Wen; Beiping Tan; Hongyu Liu; Yi Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

High-value utilization of boron mud waste: preparation of magnesium oxysulfate cement after primary blank roasting and secondary (NH4)2SO4 roasting - Jing Wen; Hongyu Sui; Tao Jiang; Lin Li; Xinyu An (Process Safety and Environmental Protection, 2024)

Characteristic changes in compound drought and heatwave events under climate change - Chuan Wang; Zhi Li; Yaning Chen; Lin Ouyang; Hongyu Zhao; Jianyu Zhu; Jiayou Wang; Yazhou Zhao (Atmospheric Research, 2024)

Carbon flow, energy metabolic intensity and metagenomic characteristics of a Fe (III)-enhanced anerobic digestion system during treating swine wastewater - Hongyu Xie; Yuzheng Wang; Yuqi Chen; Yong Hu; Rasheed Adeleke; Linda Obi; Yuanpeng Wang; Wenzhi Cao; Jih-Gaw Lin; Yanlong Zhang (Science of The Total Environment, 2024)

Numerical and experimental study on designs and performances of multi-serpentine flow field with bend-area block for proton exchange membrane fuel cell - Peijian Lin; Guoling Zhang; Dehui Yang; Yang Zhao; Hongyu Wang; Guogang Yang; Shian Li; Juncai Sun (Fuel, 2024)

National-scale 10 m annual maize maps for China and the contiguous United States using a robust index from Sentinel-2 time series - Yingze Huang; Bingwen Qiu; Peng Yang; Wenbin Wu; Xuehong Chen; Xiaolin Zhu; Shuai Xu; Laigang Wang; Zhanjie Dong; Jianyang Zhang; Joe Berry; Zhenghong Tang; et al. (Computers and Electronics in Agriculture, 2024)

Constructing blocked-nanolayer by surface charge inversion over anion exchange membrane for improved antifouling performance - Dan Lu; Hongyu Jin; Yunchen Mao; Yukun Qian; Ge Li; Jing Wang; Ying Mei; Zhikan Yao; Zhuofan Gao; Lin Zhang (Desalination, 2024)

Bruton tyrosine kinase degrader BP001 attenuates the inflammation caused by high glucose in raw264.7 cell - Jun Lin; Zhendong Chen; Yinying Lu; Hongyu Shi; Pei Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

Packing blockage and power generation of constructed wetland coupled microbial fuel cell systems using biochar as electrode and filler with different ratios - Hongyu Xin; Rui Yang; Chunyang Lin; Jingjing Zhan; Qiao Yang (Chemical Engineering Journal, 2024)

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Aeromonas salmonicida subsp. Masoucida causes an emerging infectious diseases and immune response in red swamp crayfish (Procambarus clarkii) - Yibin Yang; Tao Mao; Bin Xu; Xia Zhu; Lin Zhang; Ying Huang; Hongyu Zhang; Jin Xu; Xiaohui Ai (Aquaculture, 2024)

Degradation of iopamidol in the permanganate/sulfite process: Evolution of iodine species and effect on the subsequent formation of disinfection by-products - Yimin Lin; Hongyu Dong; Yating Zhu; Gongming Zhou; Junlian Qiao; Xiaohong Guan (Journal of Environmental Sciences, 2024)

Deterministic factors modulating assembly of groundwater microbial community in a nitrogen-contaminated and hydraulically-connected river-lake-floodplain ecosystem - Zhiyuan Qiao; Yizhi Sheng; Guangcai Wang; Xianglong Chen; Fu Liao; Hairu Mao; Hongyu Zhang; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Journal of Environmental Management, 2023)

Functional characterization of SlGSTD3 and SlGSTD4 associated with phoxim and chlorpyrifos resistance in Spodoptera litura - Li Xu; Hongyu Liu; Tao Yang; Chengshuai He; Bo Li; Genmiao Song; Lin Zhou; Runqiang Liu (Journal of Asia-Pacific Entomology, 2023)

Holocene Evolution of the Pearl River Delta: Mapping Integral Isobaths and Delta Progradation - Yongjie Tang; Zhuo Zheng; Kangyou Huang; Cong Chen; Zhen Chen; Hongyu Lu; Weisheng Wu; Xiaoming Lin; Xianhe Zhang; Hongwei Li (Journal of Marine Science and Engineering, 2023)
The Pearl River Delta (PRD, China) has undergone complex geological development within a multi-island faulted basin, shaped by the interplay of regional tectonic movements, Quaternary sea-level fluctuations, and fluvial-marine interactions. Despite a great number of studies on the Holocene sedimentary sequences and spatial differences of lithofacies and environments, scant attention has been paid to the overarching human influence on deltaic evolution and coastline modifications since the Neolithic epoch. To further elucidate the spatial variation in Holocene sedimentation and its underlying basement topography shaped during the Last Glacial Maximum (LGM), we compiled a comprehensive dataset incorporating borehole data from over 2800 cores (the maximum depth can reach 92.5 m) within the PRD. Subsequently, high-resolution isobath maps of Quaternary deltaic deposits were generated, offering unprecedented insights into sediment distribution. This dataset facilitated a nuanced reconstruction of pre-Holocene topography, revealing a zone characterized by elongated, deep-incised valleys governed by NW-SE fault orientations. Further, we delineated coastline shifts since the period of maximum Holocene transgression (~7000 years BP), contributing to an enhanced understanding of the formation and evolutionary patterns of the delta and river network oscillations. Our findings illuminate an increasing anthropogenic impact on the rate of fluvial sedimentation and land growth, particularly accentuated over the last two millennia, favoring deltaic accretion.

Two-stage electric vehicle charging optimization model considering dynamic virtual price-based demand response and a hierarchical non-cooperative game - Hongyu Lin; Jialu Dang; Haowei Zheng; Lujin Yao; Qingyou Yan; Shenbo Yang; Hongzhen Guo; Amjad Anvari-Moghaddam (Sustainable Cities and Society, 2023)

Boron nitride aerogels incorporated with metal nanoparticles: Multifunctional platforms for iodine capture and detection - Gen Li; Jianli Liang; Jing Lin; Hongyu Li; Yan Liu; Guoyang Xu; Chao Yu; Zhonglu Guo; Chengchun Tang; Yang Huang (Journal of Hazardous Materials, 2023)

“Turn-on” fluorescent sensor for oleanolic acid based on o-phenyl-bridged bis-tetraphenylimidazole - Hanqing Wu; Linlu Zheng; Liangbin Lin; Hongyu Guo; Fafu Yang (Food Chemistry, 2023)

Soil carbon-fixing bacterial communities respond to plant community change in coastal salt marsh wetlands - Qihang Liao; Chao Lu; Feng Yuan; Qinya Fan; Hongyu Chen; Lin Yang; Penghua Qiu; Ziyue Feng; Chenglong Wang; Xinqing Zou (Applied Soil Ecology, 2023)

Drip fertigation sustains crop productivity while mitigating reactive nitrogen losses in Chinese agricultural systems: Evidence from a meta-analysis - Jing Zheng; Minghua Zhou; Bo Zhu; Junliang Fan; Hongyu Lin; Bing Ren; Fucang Zhang (Science of The Total Environment, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Hemocyte proliferation is associated with blood color shade variation in the blood clam, Tegillarca granosa - Zexin Yang; Xin He; Hongyu Jin; Dan Su; Zhihua Lin; Hongxing Liu; Yongbo Bao (Aquaculture, 2023)

D-A non-equivalent random strategy to achieve donor polymers for stable organic solar cells with efficiency over 17% - Xin Lin; Silong Tu; Liren Xiao; Hongyu Zhen; Wen Wang; Qidan Ling (Chemical Engineering Journal, 2023)

A method for characterizing the deformation localization in granular materials using the relative particle motion - Dechun Lu; Hongyu Dong; Qingtao Lin; Caixia Guo; Zhiwei Gao; Xiuli Du (Computers and Geotechnics, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Exposure of ambient PM2.5 during gametogenesis period affects the birth outcome: Results from the project ELEFANT - Liqiong Guo; Huishu Lin; Hongyu Li; Xiaobin Jin; Lei Zhao; Penghui Li; Naiwei Xu; Song Xu; Junkai Fang; Shaowei Wu; Qisijing Liu (Environmental Research, 2023)

A novel criterion for yield shear displacement of rock discontinuities based on renormalization group theory - Shijie Xie; Hang Lin; Hongyu Duan (Engineering Geology, 2023)

Development and application of DETECTR-based rapid detection for pathogenic Bacillus anthracis - Jianhao Xu; Xinru Bai; Xianglilan Zhang; Bing Yuan; Lei lin; Yan Guo; Yujun Cui; Jinxiong Liu; Hongyu Cui; Xiangang Ren; Jinglin Wang; Yuan Yuan (Analytica Chimica Acta, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Desulfurization performance of chemical looping conversion using red mud as an oxygen carrier - Hongming Jiang; Shuchang Yan; Jingzhi Yan; Chengyang Li; Yan Lin; Zengli Zhao; Zhen Huang; Hongyu Huang; Haibin Li (Chemical Engineering Journal, 2023)

The hybrid Pelteobagrus fulvidraco (♀) × Leiocassis longirostris (♂) exhibits improved trait on hypoxia-tolerance - Hongyu Wang; Ge Lin; Jie Zhou; Yongqin Zong; Xianhui Ning; Tao Wang; Shaowu Yin; Kai Zhang; Jie Ji (Aquaculture, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Photodegradation of biobased polymer blends in seawater: A major source of microplastics in the marine environment - Shasha Zhao; Liuqingqing Liu; Chenguang Li; Hao Zheng; Yadan Luo; Lihua Pang; Qianhui Lin; Hongyu Zhang; Cuizhu Sun; Lingyun Chen; Fengmin Li (Frontiers in Marine Science, 2022)
Introduction Biobased polymer blends have been recommended as an eco-friendly solution to abate plastic pollution in the environment. However, the formation of microplastics (MPs) by photodegradation of biobased polymer blends in the marine environment is still not well understood. In this study, we investigated the formation of MPs and the changes in the physicochemical properties of three types of biobased polymer blends after photodegradation in seawater. Methods The investigated materials included non-biodegradable polyethylene/ thermoplastic starch blends (PE/TPS) and polypropylene/thermoplastic starch blends (PP/TPS), as well as biodegradable polylactic acid/poly (butylene adipate-co-terephthalate)/thermoplastic starch blends (PLA/PBAT/TPS). The control groups were the corresponding neat polymers, including polyethylene (PE), polypropylene (PP), and polylactic acid (PLA). Results The size distribution of the pristine and aged MPs indicated that the polymer blends were more likely to produce small-sized particles after photodegradation due to their poorer mechanical properties and lower resistance to UV irradiation than the neat polymers. Noticeable surface morphology alterations, including cracks, holes, and pits, were observed for polymer blends after photodegradation, while neat polymers were relatively resistant. After photodegradation, the attenuated total reflection Fourier transformed infrared spectroscopy (ATR-FTIR) spectrum of the polymer blends showed a significant decrease in the characteristic bands of thermoplastic starch (TPS), indicating depletion of their starch fractions. The C1s spectra of the polymer blends demonstrated that the aged MPs contained fewer -OH groups than the pristine MPs, further confirming the photodegradation of TPS. The molecular weight distribution curve of the polymer blends shifted significantly towards low molecular weight, suggesting the occurrence of chain scission during photodegradation. These results indicate that the polymer blends have a higher degree of photodegradation than neat polymers, and thereby generate more small-sized MPs than neat polymers. Photodegradation caused changes in the contact angle and surface charge of MPs derived from biobased polymer blends, which may affect the vector effects of MPs on any coexisting pollutants. Discussion In summary, polymer blends may pose a higher risk to the marine environment than neat polymers, and caution should be taken in promoting biobased polymer blends.

CircPVT1 facilitates the progression of oral squamous cell carcinoma by regulating miR-143-3p/SLC7A11 axis through MAPK signaling pathway - Shiliang Wang; Wenlu Li; Long Yang; Jianqiao Yuan; Lin Wang; Na Li; Hongyu Zhao (Functional & Integrative Genomics, 2022)

Quantitative synthetic MRI reveals grey matter abnormalities in children with drug-naïve attention-deficit/hyperactivity disorder - Shu Su; Yingqian Chen; Yan Dai; Liping Lin; Long Qian; Qin Zhou; Mengsha Zou; Hongyu Zhang; Meina Liu; Xianhong Xiang; Zhiyun Yang (Brain Imaging and Behavior, 2022)

Identification and Characterization of Gene SpDMRT99B and Its Sex-Biased Expression Profile in the Mud Crab, Scylla paramamosain - Yin Zhang; Shaobin Fang; Fei Lin; Shengkang Li; Huaiping Zheng; Yueling Zhang; Mhd Ikhwanuddin; Hongyu Ma (Journal of Ocean University of China, 2021)

Identification of a recessive gene YrZ15-1370 conferring adult plant resistance to stripe rust in wheat-Triticum boeoticum introgression line - Minghu Zhang; Xin Liu; Ting Peng; Dinghao Wang; Dongyu Liang; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Theoretical and Applied Genetics, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

The hand-arm vibration syndrome associated with the grinding of handheld workpieces in a subtropical environment - Nuoyan Wei; Hansheng Lin; Ting Chen; Bin Xiao; Maosheng Yan; Li Lang; Hongyu Yang; Shan Wu; Paul-Émile Boileau; Qingsong Chen (International Archives of Occupational and Environmental Health, 2021)

Identification and Sexually Dimorphic Expression of a FoxL2-like Gene in Mud Crab (Scylla paramamosain): Potential Roles in Male Differentiation and Development - Yuying Yuan; Jiali Lin; Xueying Tan; Xi Shi; Shaobin Fang; Yin Zhang; Hongyu Ma; Fan Lin (Thalassas: An International Journal of Marine Sciences, 2021)

Cu2+ Inhibits the Peroxidase and Antibacterial Activity of Homodimer Hemoglobin From Blood Clam Tegillarca granosa by Destroying Its Heme Pocket Structure - Sufang Wang; Xiaopei Yu; Shunqin Zhang; Hongyu Jin; Zhongfa Chen; Zhihua Lin; Yongbo Bao (Frontiers in Marine Science, 2021)
Beyond its role as an oxygen transport protein, the homodimer hemoglobin of blood clam Tegillarca granosa (Tg-HbI) has been found to possess antibacterial activity. However, the mechanism of antibacterial activity of Tg-HbI remain to be investigated. In this study, we investigated the effects of Cu 2+ on the structure, peroxidase activity, and antibacterial ability of Tg-HbI. Tg-HbI was significantly inactivated by Cu 2+ in a non-competitive inhibition manner, following first-order reaction kinetics. The Spectroscopy results showed that Cu 2+ changed the iron porphyrin ring and the coordination of heme with proximal histidine of Tg-HbI, and increased the hydrophobicity of heme pocket. We found that proline could stabilize the heme pocket structure of Tg-HbI, hence, protect peroxidase activity and antimicrobial activity of Tg-HbI against damage by Cu 2+ . Our results suggest that Cu 2+ inhibits the peroxidase and antibacterial activity of Tg-HbI by destroying its heme pocket structure and Tg-HbI probably plays an antibacterial role through its peroxidase activity. This result could provide insights into the antibacterial mechanism of Tg-HbI.

Irregular structural networks of gray matter in patients with type 2 diabetes mellitus - Chuanlong Cao; Wanqing Liu; Qing Zhang; Jian-lin Wu; Yumei Sun; Danyang Li; Hongyu Fan; Feifei Wang (Brain Imaging and Behavior, 2020)

Molecular cloning, characterization and expression profiles of a SoxB2 gene related to gonadal development in mud crab ( Scylla paramamosain ) - Jiali Lin; Yuying Yuan; Xi Shi; Shaobin Fang; Yin Zhang; Mengyun Guan; Zhuofang Xie; Hongyu Ma; Fan Lin (Invertebrate Reproduction & Development, 2020)

Neighboring genes are closely related to whole genome duplications after their separation - Shuaibin Lian; Tianliang Liu; Zaibao Zhang; Hongyu Yuan; Lei Wang; Lin Cheng (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Quantitative phosphoproteomic analyses provide evidence for extensive phosphorylation of regulatory proteins in the rhizobia–legume symbiosis - Zaibao Zhang; Danxia Ke; Menghui Hu; Chi Zhang; Lijun Deng; Yuting Li; Jiuli Li; Hai Zhao; Lin Cheng; Lei Wang; Hongyu Yuan (Plant Molecular Biology, 2019)

Three-dimensional Forest growth simulation in virtual geographic environments - Liyu Tang; Xianmin Peng; Chongcheng Chen; Hongyu Huang; Ding Lin (Earth Science Informatics, 2019)

Comparative Transcriptome Analysis Provides Insights into Differentially Expressed Genes and Long Non-Coding RNAs between Ovary and Testis of the Mud Crab (Scylla paramamosain) - Xiaolong Yang; Mhd Ikhwanuddin; Xincang Li; Fan Lin; Qingyang Wu; Yueling Zhang; Cuihong You; Wenhua Liu; Yinwei Cheng; Xi Shi; Shuqi Wang; Hongyu Ma (Marine Biotechnology, 2018)

Anti-Collision Assessment and Prediction Considering Material Corrosion on an Offshore Protective Device - Ang Qiu; Xiangxi Han; Hongyu Qin; Wei Lin; Youhong Tang (Journal of Marine Science and Engineering, 2017)
Corrosion deterioration of steel can heavily degrade the performance of marine and offshore structures. A typical steel protective device, which has worked for a dozen years in a river estuary, is selected as the research object. Its current corrosion response is measured on site and its further corrosive response is predicted based on measurement data and the structure’s current state. Nonlinear finite element method is utilized to analyze the degradation of the protective device’s anti-collision performance. Meanwhile the rubber buffer effect has been investigated for its anti-collision on the protective device. A prediction method is proposed that can accurately forecast degradation of the anti-collision performance of a protective device as time progresses.

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Incorporating functional annotation information in prioritizing disease associated SNPs from genome wide association studies - Lin Hou; TianZhou Ma; HongYu Zhao (Science China Life Sciences, 2014)

Clinically Relevant Reperfusion in Acute Ischemic Stroke: MTT Performs Better than Tmax and TTP - Andria L. Ford; Hongyu An; Linglong Kong; Hongtu Zhu; Katie D. Vo; William J. Powers; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2014)

Effect of dietary potassium on growth, nitrogen metabolism, osmoregulation and immunity of pacific white shrimp (Litopenaeus vannamei) reared in low salinity seawater - Hongyu Liu; Xinjie Zhang; Beiping Tan; Yingbo Lin; Shuyan Chi; Xiaohui Dong; Qihui Yang (Journal of Ocean University of China, 2014)

More insights into early brain development through statistical analyses of eigen-structural elements of diffusion tensor imaging using multivariate adaptive regression splines - Yasheng Chen; Hongtu Zhu; Hongyu An; Diane Armao; Dinggang Shen; John H. Gilmore; Weili Lin (Brain Structure and Function, 2014)

Transcriptional responses to drought stress in root and leaf of chickpea seedling - Xiansheng Wang; Ying Liu; Yuying Jia; Hanyan Gu; Hongyu Ma; Tian Yu; Hua Zhang; Quanjia Chen; Lin Ma; Aixing Gu; Jusong Zhang; Shubing Shi; et al. (Molecular Biology Reports, 2012)

Defining the Ischemic Penumbra Using Hyperacute Neuroimaging: Deriving Quantitative Ischemic Thresholds - Andria L. Ford; Hongyu An; Katie D. Vo; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2012)

Noninvasive Measurements of Cerebral Blood Flow, Oxygen Extraction Fraction, and Oxygen Metabolic Index in Human with Inhalation of Air and Carbogen using Magnetic Resonance Imaging - Hongyu An; Souvik Sen; Yasheng Chen; William J. Powers; Weili Lin (Translational Stroke Research, 2012)

Oxygen Metabolism in Ischemic Stroke Using Magnetic Resonance Imaging - Hongyu An; Qingwei Liu; Yasheng Chen; Katie D. Vo; Andria L. Ford; Jin-Moo Lee; Weili Lin (Translational Stroke Research, 2012)

Expression, Purification, and Characterization of an Iron Chaperon Protein CyaY from Acidithiobacillus ferrooxidans - Chenbing Ai; Hongyu Mo; Qian Chen; Yuandong Liu; Lin Tang; Juan Du; Jia Zeng (Current Microbiology, 2011)